2021
DOI: 10.1007/s10725-021-00763-z
|View full text |Cite
|
Sign up to set email alerts
|

Integration of transcriptome and proteome analysis reveals the mechanism of freezing tolerance in winter rapeseed

Abstract: Winter rapeseed seedlings are susceptible to low temperature during overwintering in Northwest China, leading to reduced crops production. Freezing stress is one of the utmost environmental stresses in Northwest China from late autumn to early spring, which are eventful for overwinter survival rate of winter rapeseed. However, the molecular mechanism of freezing tolerance formation is still very backward in winter rapeseed. In this study, using a pair of freezing-sensitive and freezing-resistant cultivars NQF2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 70 publications
(60 reference statements)
1
9
0
Order By: Relevance
“…Freezing stress can cause a set of physiological and morphological changes, leading to the accumulation of many protective substances in plants ( Gao et al, 2019 ). Freezing stress also results in membrane lipid peroxidation and cellular ultrastructure damage ( Deng et al, 2015 ; Shi et al, 2018 ), which was comparable with our previous researches ( Wei et al, 2021a ; Wei et al, 2021b ). In this study, under freezing stress, the 15NS plant showed obvious wilting, whereas no significant changes were found in the 16NS and 17NS plants, in compared with controls ( Figure 1A ), which implied that freezing stress was enhanced year by year.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Freezing stress can cause a set of physiological and morphological changes, leading to the accumulation of many protective substances in plants ( Gao et al, 2019 ). Freezing stress also results in membrane lipid peroxidation and cellular ultrastructure damage ( Deng et al, 2015 ; Shi et al, 2018 ), which was comparable with our previous researches ( Wei et al, 2021a ; Wei et al, 2021b ). In this study, under freezing stress, the 15NS plant showed obvious wilting, whereas no significant changes were found in the 16NS and 17NS plants, in compared with controls ( Figure 1A ), which implied that freezing stress was enhanced year by year.…”
Section: Discussionsupporting
confidence: 91%
“… Liu et al (2017) showed that the DNA methylation patterns were changed in rapeseed under freezing treatment by whole genome bisulfite sequencing (WGBS). Wei et al (2021b) identified some DMGs involved in freezing response in developing rapeseed leaves by integrated transcriptome and methylome analysis. However, these studies were mainly subjected to the screening of a broad range of epigenetically regulated genes, and the evolutionary mechanism of how DNA methylation regulates genes to enhance freezing resistance of winter rapeseed was still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, our research group has successfully selected and bred rapeseed cultivars of B. napus that can overwinter safely in most of the northwestern areas from the 38° to the 42° north latitude, where the lowest temperature in winter is -26℃ [15,16]. Moreover, the cold tolerance characteristics of these rapeseed cultivars at the transcription, protein, physiological, biochemical, and subcellular levels were studied [15,21,22]. The strong coldresistant cultivar had stronger antioxidant enzyme activity and accumulation of cryoprotective molecules, associated with the metabolic pathways, including alpha-linolenic acid metabolism, plant hormone signal transduction, microbial metabolism in diverse environments, linoleic acid metabolism, phenylpropanoid biosynthesis, glutathione metabolism, flavonoid biosynthesis metabolism, and amino acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…AP2-EREBP (APETALA2/ethylene-responsive element-binding protein) TFs are important and have played a crucial role in loquat fruitlet transcription profiling under freezing stress tolerance [ 41 ]. AP2/ERF TFs were also found in winter rapeseed transcriptome under freezing tolerance [ 43 ]. AP2-EREBP could be sub-classified into four sub-families, i.e., DREB/CBF, ERF, CBF, and RAP [ 44 ], whereas DREB/CBF TFs have demonstrated their indispensable role in low-temperature stress in the tea plant [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protein that contained at least one unique peptide was set as necessary for the identified proteins. In order to control the rate of false-positives at the protein level, the false discovery rate (FDR) was set at less than 1%, with confidence intervals higher than 95% [ 43 ]. However, sequences of positively identified proteins were further carried out for BLAST searching of the UniProt database.…”
Section: Methodsmentioning
confidence: 99%